Husband’s support towards unmet need family planning incidence on couples of childbearing age in Denpasar city - Wayan, Ari Adiputri Ni; Kadek, Widiantari (International Journal of Research in Medical Sciences, 2020)
Background: Husband’s support is the most important role in decision making in the family, especially when deciding to use contraceptives. Methods: The research design was analytic observational study with a cross sectional study approach. The population in this study were all couples of childbearing age in the city of Denpasar for the period 2020 and the number of samples in the study was 96 couples of childbearing age. The sampling technique used was proportional stratified random sampling. The data collection method was carried out by distributing online questionnaires (Google form). The data analysis technique used was descriptive univariate analysis and bivariate analysis using chi-square analysis. Results: Most of the couples of childbearing age that is 55 people who received support from their husbands, had used contraceptives as many as 40 people (72.7%). Respondents of couples of childbearing age who do not get support from their husbands are 41 people and do not use contraceptives (unmet need) as many as 33 people (80.5%). The results of bivariate analysis using chi square analysis showed a significant relationship with a value of p=0.000 (p<0.05). Conclusions: There is a significant relationship between husbands’ support with the incidence of unmet need in couples of childbearing age. Pair counselling is very necessary for husbands to increase their knowledge of the importance of using contraceptives.